2015
DOI: 10.12665/j134.langer
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmaceutical Manufacturing: Historical and Future Trends in Titers, Yields, and Efficiency in Commercial-Scale Bioprocessing

Abstract: his article documents the progress, current state, and projected future trends in titer and yield as industrial and technological benchmarks for commercial-scale biopharmaceutical manufacture. Biopharmaceutical product commercial-scale manufacturing (bioprocessing) was benchmarked by tracking titers and yields over time, from the 1980s to the present, and further out ten years. This study compiled commercial-scale titer and yield data for a set of 39 major biopharmaceuticals, nearly all mammalian-expressed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Industrial pharmaceutical showed almost up to 50-60% of approved recombinant proteins and antibodies were produced in mammalian-based cell system. 21 HEK293T is among several cell lines derived from a human mammalian cell that used for the production of recombinant antibody. Frank Graham established human embryonic kidney 293 (HEK293) cells in 1973 at experiment number 293 by using DNA of Adenovirus 5.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial pharmaceutical showed almost up to 50-60% of approved recombinant proteins and antibodies were produced in mammalian-based cell system. 21 HEK293T is among several cell lines derived from a human mammalian cell that used for the production of recombinant antibody. Frank Graham established human embryonic kidney 293 (HEK293) cells in 1973 at experiment number 293 by using DNA of Adenovirus 5.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins expressed in E. coli which have been purified using the ELP technology have reported yields of up to 500 mg of target protein per liter of culture medium (Hassouneh et al, ; Nettles et al, ) (Table ), which is comparable to the titers obtained for some biopharmaceutical proteins (refer to industry survey provided in the following articles (Fox, ; Langer and Rader, )). For example, Chow et al () demonstrated that ∼400–500 mg GFP per liter of culture could be obtained when GFP is fused to an ELP and expressed in E. coli using optimized medium conditions (as high as 1.6 g of GFP‐ELP was obtained per liter of optimized culture medium; molecular weight of GFP to ELP = 30:35.5; if GLP is cleaved from ELP with 50–65% protease efficiency, ∼400–500 mg of GFP is expected).…”
Section: Considerations For Translating Elpylation To Biopharmaceuticmentioning
confidence: 90%
“…The manufacturing methods of biotherapies are considerably more complicated and expensive than traditional small molecule therapies, which could in part account for the increasing cost of the end product. However, the efficiency of manufacture of biopharmaceuticals has increased dramatically over the same period: with typical yields increasing from 1 to 2.5 g/l during the period 2001-2014 [80]. The complexity of manufacture also creates an additional barrier to entry for new drug manufacturers.…”
Section: Balancing the Economics And Promise Of Personalised Oncologymentioning
confidence: 99%